Comparative study of amino acid mixtures in hypermetabolic patients - Bertullo, Hugo; Muguruza, Alvaro (Cirugía del Uruguay, 1986)
Prospective test wlth two groups of patlents, predominantly surgical, was carried out in order to determine the utility and lack of complications of the nitrogen sources, for parenteral nutrition, under the control of the U.N.E. of C.A.S.M.U. Once the inltial nutritlonal condition and the agresslon by both groups were determined, the degree of hipermetabolism, causes of the difficulty in making the nitrogenized balances positive and visceral incldence in each of them were estimated. Results show significant differences In the two groups but allow to conclude that both preparations are useful, that they lack contraindications and that both have contrlbuted to the acceptable evolutions achieved.